Peningkatan Kompetensi Guru PAUD Melalui Pelatihan Menciptakan Educational Cloth Book - Astuti, Retno Dwi; Leksana, Dinar Mahdalena; Febriani, Nur Hida (LP2M INSURI Ponorogo, 2023)
This community service activity aims to broaden PAUD teachers' insights about tools and materials that can be used to create Educational Cloth Books in improving skills in making teaching aids in early childhood education. Educational Cloth Books are books made of soft cloth and filled with soft polyester fiber-like pillows that can be used as educational aids at the early childhood education level. The Educational Cloth Book is accompanied by funny pictures and adapted to the theme and uses a simple story method so that it is easy for children to understand. The method used in this activity included identifying participants, organizing, namely negotiating with related parties, explaining, introducing the Educational cloth book model, demonstrating how to make it, and then the participants made an Educational cloth book. The results of the training showed that PAUD teachers in Tikung District received additional knowledge about making teaching aids in the form of Educational Cloth Books, being able to create Educational Cloth Books with various themes to be applied to teaching institutions so that learning becomes more meaningful and fun for children. In addition, teachers can develop RPPH (Daily Learning Implementation Plans) that can be applied to the learning process and train creative teachers to create educational teaching aids with materials from the surrounding environment. After implementing this community service, it is suggested to PAUD teachers apply the knowledge and skills acquired in their respective schools to improve the quality of learning at PAUD institutions